PENGARUH PENERAPAN STRATEGI FIRING LINE TERHADAP PEMAHAMAN SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VII DI SMP N SUKARAYA KECAMATAN KARANG JAYA KABUPATEN MUSI RAWAS - Santi Hajri Yanti; Akmal Hawi; Syarnubi Syarnubi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2021)
The low understanding of students can be influenced by several factors, namely internal and external factors, and one of the main causes of learning difficulties for students is external factors, such as the use of methods or learning strategies that are wrong, which can make students become bored and less interested in follow the learning process, so that it can affect the understanding of students. This study aims to determine the understanding of Islamic Religious Education by applying the firing line strategy in SMP N Sukaraya, to find out the understanding of Islamic Religious Education without applying the firing line strategy in SMP N Sukaraya and whether there is an effect of applying the firing line strategy to the understanding of Islamic Religious Education students in SMP N 6 Palembang.This research uses experimental research, with a population of 50 students from 2 classes and a sample of 25 experimental class students and 25 control class students using saturated sampling techniques.The results of this study were obtained: 1) the students' understanding of the experimental class was in the high category there were 5 students (20%), for the students' understanding of the moderate category were 13 students (52%) and the students' understanding of the PAI category in the low category were 7 people (28%). 2) understanding of control class students in the high category there are 3 students (12%), for understanding students in the medium category are 19 students (76%) and understanding of PAI students in the low category there are 3 people (12%). 3) There is an effect of the application of the firing line strategy to the understanding of Islamic Religious Education students in SMP N Sukaraya seen from the value of the t test which shows that tcount is greater than ttable namely tcount = 3.89 and ttable = 2.40 with a significant level of 1% so the results t test states that the alternative hypothesis is accepted and the null hypothesis is rejected.